Influence of the w/c ratio on the hydration process of a magnesium phosphate cement and on its retardation by boric acid. (July 2018) - Lahalle, Hugo; Cau Dit Coumes, Céline; Mercier, Cyrille; Lambertin, David; Cannes, Céline; Delpech, Sylvie; Gauffinet, Sandrine
Abstract: Magnesium potassium phosphate cements (MKPCs) are prepared using calcined magnesia (MgO) and an acidic solution of potassium dihydrogen phosphate (KH2 PO4 ). Their fast setting and high heat of hydration can be problematic when large volumes of materials are produced. Boric acid (B(OH)3 ) is thus commonly added as a set retarder. This work investigates MKPC hydration in paste (water-to-cement ratio w/c = 1) and its retardation by B(OH)3 . The precipitation of K-struvite (MgKPO4 ·6H2 O) is preceded by that of phosphorösslerite (MgHPO4 ·7H2 O) and Mg2 KH(PO4 )2 ·15H2 O. Cattiite (Mg3 (PO4 )2 ·22H2 O), an end-product in diluted suspension (w/c = 100), is not observed. B(OH)3 slows down the formation of hydrates in two ways: ( i ) by stabilizing in solution the cations that outbalance the negative charges of the polyborates formed at pH above 6, and ( ii ) through the precipitation of an amorphous mineral containing borate and orthophosphate. The first process occurs both in diluted suspensions and pastes, the second is specific to pastes.